Spectroscopic Analysis and Dynamics of Dissolved Organic Carbon from an Oil Palm Plantation Peatland - Untung Sudadi; Ahmad Imtaz Sumbari; Budi Nugroho (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Drainage following conversion of peatlands to oil palm plantations is always associated with carbon (C) loss, one of which is dissolved organic carbon (DOC). Analytical procedure commonly used to determine DOC is the high-temperature combustion (HTC) method, which requires an expensive instrument. An alternative low-cost method has been developed. The objectives of this research were to determine and validate the most suitable UV-Vis spectrophotometer’s wavelength for estimating DOC concentration and evaluating its dynamics from an oil-palm plantation Indonesian-peatland. The DOC concentrations were measured on ground water and canal water samples at wavelengths of 254, 270, and 350 nm and the analytical results were then validated against those reference values resulted from the use of HTC method using Total Organic Carbon Analyzer (TOC Analyzer), based on simple regression analysis. The results showed that the most suitable wavelength for estimating DOC concentration using UV-Vis spectrophotometer was 350 nm. The DOC concentration in groundwater (35.67 ± 8.40 mg L-1) were around two times greater than in canal water (16.26 ± 4.15 mg L-1). The DOC flux from the research area were at the range of 0.66 ˗ 1.15 g C m-2 month-1, with an average of 0.85 g C m-2 month-1.